2019
DOI: 10.1016/j.amc.2018.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Restricted r-Stirling numbers and their combinatorial applications

Abstract: We study set partitions with r distinguished elements and block sizes found in an arbitrary index set S. The enumeration of these (S, r)-partitions leads to the introduction of (S, r)-Stirling numbers, an extremely wide-ranging generalization of the classical Stirling numbers and the r-Stirling numbers. We also introduce the associated (S, r)-Bell and (S, r)-factorial numbers. We study fundamental aspects of these numbers, including recurrence relations and determinantal expressions. For S with some extra stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In other words, the graph Θw is integral if and only if w = t + . Recently, Beáta et al [3] have shown a combinatorial…”
Section: If R = Then G W Is Not An Integral Graph But It Does Have mentioning
confidence: 99%
“…In other words, the graph Θw is integral if and only if w = t + . Recently, Beáta et al [3] have shown a combinatorial…”
Section: If R = Then G W Is Not An Integral Graph But It Does Have mentioning
confidence: 99%
“…If we require each block/cycle/ordered block (not only the non-distinguished ones) to contain at least s elements, then we call them n, m, r , D A ≥s, * n, m, r , DL ≥ s, * n, m, r , respectively. Alternative s-associated r -Bell numbers appear in two recent papers [1,3] (the former one allows a more general restriction on the cardinality of the blocks), while in [19,24], the authors investigated alternative 2-associated and alternative s-associated r -factorials under the names of r -derangement and generalized r -derangement numbers.…”
Section: Alternative Definitionsmentioning
confidence: 99%
“…Again, B ≥ 1 n, r = B n, r . After the completion of this article, we have learnt about two very recent papers [1,3] which deal with associated r -Bell numbers, but in an alternative way, see the closing section of the present paper about alternative definitions. Now, we turn our attention to the "Bell-like numbers of the first kind", the permutational variants of the above numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Choi and Smith [5] considered r-restricted Stirling numbers of the second kind and those partitions that each block contains at most r members. To see other researches on the generalization of Stirling numbers, we refer the reader to [13,14,9,7,2,1,15,11].…”
Section: Introductionmentioning
confidence: 99%